Karakteristik Silika Sekam Padi Kabupaten Cilacap Dengan Menggunakan Ekstraksi KOH Dan HCl - Nur Fitry Indah Mawarti; Riza Ma'riffathur Ramadhan; Saddam Libertyan; Dodi Satriawan (Universitas Riau, 2024)
This research aims to conduct an initial analysis of the characteristics of rice husk silica to be used as a membrane for purifying used cooking oil. Rice husks were obtained from Cilacap district. Rice husks are pyrolyzed at 650 0C for 6 hours until rice husk ash is produced. The rice husk ash is ground to a size of 50 mesh. Then 50 grams of rice husk ash was weighed and washed with 1 L of distilled water at a temperature of 80 0C. The washed ash was then extracted with 1 L of 5% KOH for 2 hours at a temperature of 75 0C. The silica extraction was divided into 5 and 10% HCL was added to obtain a pH of 4, 5, 6, 7, and 8. The analysis carried out included rice husk ash yield analysis, silica yield, water content analysis, and iodine absorption analysis. The best results were obtained at pH 8 in the silica yield obtained, the water content at pH 6 was 7.4%, and the iodine absorption capacity at pH 8 was 1271.71%.